Effect of deep cold rolling on residual stress distributions between the treated and untreated regions Ti–6Al–4V alloy - Lim, Andre (2018)
The residual stress distributions caused by the deep cold rolling (DCR) process, with a focus on the distributions at the boundary of the treatment zone, are examined in this study. A three-dimensional finite-element (FE) model, validated with experimental residual stress data, is used to study the effect of the process. The residual stress distribution in the crosswise direction (perpendicular to rolling direction) shows a region of tensile residual stress at the start and end of the track that may be a cause for concern. The reason for this region of tensile stress is likely to be due to the reduced treatment of the start and end zones due to the step over and the tool path taken. Other factors that cause a difference between the steady state and the transient zone of the burnished area are also investigated. It is shown that the net material movement causes larger plastic deformation in the boundary zone between the burnished and unburnished region of DCR.